Capital Gains Taxes and Real Corporate Investment: Evidence from Korea - Moon, Terry S. (American Economic Review, 2022)
This paper assesses the effects of capital gains taxes on investment in the Republic of Korea (hereafter, Korea), where capital gains tax rates vary at the firm level by firm size. Following a reform in 2014, firms with a tax cut increased investment by 34 log points and issued more equity by 9 cents per dollar of lagged revenue, relative to unaffected firms. Additionally, the effects were larger for firms that appeared more cash constrained or went public after the reform. Taken together, these findings are consistent with the “traditional view” predicting that lower payout taxes spur equity-financed investment by increasing marginal returns on investment. (JEL D25, G31, G32, H25, H32, L25)